Assessing the oxidising effect of NaNO3 and NaNO2 from disposed Eurobitum bituminised radioactive waste on the dissolved organic matter in Boom Clay. (May 2016) - Bleyen, N.; Vasile, M.; Mariën, A.; Bruggeman, C.; Valcke, E.
Abstract: In Belgium, compatibility studies are performed in view of the final disposal of nitrate-containing bituminised intermediate-level radioactive waste in Boom Clay, which is considered as a potential host formation. Due to the presence of large amounts of nitrate in the waste, a slow release of nitrate (and to a smaller extent also nitrite) into the Boom Clay is expected. Nitrate and/or nitrite reduction by redox-active components of the host rock may cause a geochemical perturbation of the clay and subsequently might affect its barrier function against the migration of radionuclides. This paper therefore addresses the possible oxidation of one of the main redox-active components of the Boom Clay, i.e. dissolved organic matter, by nitrate and nitrite. For this, abiotic and microbially mediated nitrate and nitrite reduction was studied during long-term batch tests (2–2.5 years) in Boom Clay pore water, containing 155 ± 15 mg C/l present as humic and fulvic acids. Changes in the reducing capacity of the DOM due to oxidation were assessed successfully using two oxidants, namely ferricyanide and ferric citrate. The results of these experiments indicate that an abiotic reaction between DOM and nitrate does not occur or is characterised by very slow kinetics. On the other hand, a slow microbial nitrate reduction to nitrite was observed and the associated oxidation of DOM was confirmed by a decrease in the (partial) reducing capacity of DOM for ferric citrate. In contrast to nitrate, nitrite was shown to oxidise DOM both abiotically and mediated by microbes through (chemo)denitrification, although these reactions also seem to occur only at a rather slow rate. No significant change in the maximally obtainable reducing capacity of DOM (using ferricyanide) was detected during any of the observed reactions, suggesting that the impact of such a slow heterotrophic nitrate reduction is very limited. Highlights: Microbial nitrate/nitrite reduction by dissolved organics (DOM) from Boom Clay. Slow abiotic nitrite, but no nitrate reduction by DOM from Boom Clay. Successful monitoring of decrease in reducing capacity of DOM due to oxidation. No decrease in maximally measurable reducing capacity of DOM due to nitrate/nitrite.